(3GdUGajs - (3eMSf eMeO Hf eQJVis
(3ChdgG (B:s
(3GdPGJ jYfj Cfg deG GeJGR Yf SGFQ CaQGO GdYGe HeG dg ef GdChUGa GdTQjaI LYd cCfg TjA BNQ eZGjQ ddYGe(B... (3JaSjQ ShQI Gdcgas
(3BNQgG (B:s
(3aPdc bhdg(B: (3hCjOge HQhM efg(B... (3cPdc ef GdfGS TjWGf jMed GdfGS Ydi GdeYGUj ceG Med GdTjWGf ef GdLf hbO eVi JaSjQ TjGWjf GdCfS aj ShQI GdCfYGe (B. (3Je cJGH GdUGajs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs